Role of Herbal Extract in Stem Cell Development - Ferry Sandra (Molecular and Cellular Biomedical Sciences, 2018)
Stem cell research has been developed and today we can witness some stem cell clinical trials are on going in Indonesia. To meet a successful stem cell treatment, several factors need to be considered, such as cell number. Cell number has been reported to be crucial, and therefore optimal cell number should be achieved. Meanwhile, in some circumstances, cell number is not enough, therefore, cell number should be enriched in an in vitro stem cell culture setting. In an in vitro stem cell culture, besides suitable and sterile equipment, reagents such as culture medium, serum and antibiotics are all important. Although all those criteria are fulfilled, somehow stem cell enrichment cannot be achieved, cell number is still below the target. Modification of stem cell microenvironment should then be an alternative. The addition of growth factors is a part of the strategies to reach a better enrichment. So that, stem cells could later be induced to proliferate at a higher rate. This strategy was then pursued by the scientist involved in herbal medicine. Herbal extracts were now highly investigated due to its potential to induce cell proliferation. Some herbal extracts inducing proliferation and differentiation of stem cell will be shown and described.Keywords: herbal extract, stem cell, progenitor cell, proliferation, differentiation